The Effectiveness of Customer Experience and Customer Value on Customer Loyalty at Cinepolis Batam with Customer Satisfaction as an Intervening Variable - Rexy Mainaki; Nur Elfi Husda (Universitas Medan Area, 2025)
The entertainment industry is currently experiencing significant growth and is increasingly in demand by both individuals and society. This study applies the theory of service marketing and customer behavior, which focuses on marketing concepts and the behavior of customers during transactions. The purpose of this research is to assess the impact of customer experience and customer value on customer loyalty, with customer satisfaction acting as an intervening variable at Cinepolis Mall Botania 2 Batam during March 2024. The population for this study consists of individuals who purchased tickets, food, and beverages during March 2024, totaling 9,083 people. The sample includes 293 respondents, representing the average audience for that period. The data analysis method involves a quantitative approach used a questionnaire and SmartPLS analysis tool. The tests conducted include validity and reliability assessments using the outer model and inner model. The findings from the data tests indicate that while customer experience does not influence customer loyalty, other hypotheses examined in the study do show a significant impact